Synthesis of FAU(Y)- and MFI(ZSM5)-nanosized crystallites for catalytic cracking of 1,3,5-triisopropylbenzene - Morales-Pacheco, P. (2011)
Nanocrystals of FAU(Y) and MFI(ZSM5) zeolites were synthesized from clear solutions at 80-95 °C under autogen and atmospheric pressures, respectively. The X-ray diffraction (XRD) patterns confirm the structural features reported for FAU(Y) and MFI(ZSM5). Similarly, Fourier transform infrared spectroscopy (FTIR) with KBr shows the bands arising from typical structural groups of FAU(Y) and MFI(ZSM5), i.e., 455-462 cm-1 and 555-560 cm-1. The mean crystallites size was measured by transmission electron microscopy (TEM) and it was determined also by Rietveld's method using Scherrer's equation; with similar results between 20 and 40 nm. Also, a cubic morphology for FAU(Y) crystallites and a disk-like habit for MFI(ZSM5) were verified together with the typical dimensions of the pore system and symmetry, i.e., pore diameters were between 0.74 and 0.56 nm for FAU(Y) and MFI(ZSM5). Theoretical images were calculated using HRTEM (Cerius2) program and these were compared with the experimental ones, thus matching the corresponding typical structural parameters. The textural properties were determined by N2 adsorption-desorption (BET) and typical surface areas of 658 and 495 m 2/g were obtained for the nanosized materials. After ion-exchanging NH4NO3 ammonia was removed by calcination (i.e., 550 °C) and the total acidity was measured, i.e. 1190 and 1084 μmol(Py)/g (cat) at 25 °C and 84 and 34 μmol(Py)/g (cat) at 400 °C for FAU(Y) and MFI(ZSM5), respectively. Thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC) in air and N2 atmospheres showed a thermal stability of these materials up to about 1000 °C. The catalytic activity of FAU(Y) and MFI(ZSM5) was tested by means of the cracking of 1,3,5-triisopropylbenzene (1,3,5-TIPBz) in a CREC Riser Simulator Reactor at 350 °C; the cracking of 1,3,5-TIPBz increased to about 0.6 and 1.3 times from big (108.9 and 82.8 nm) to small (18 and 20.7 nm) crystallites of FAU(HY) and MFI(HZSM5), respectively, while diffusivity increased to about 3 and 4.6 times, which demonstrates a correlation between the mean crystallite size of these zeolites with cracking activity from the external crystallite surface and the diffusivity of large reactive molecules, i.e., 1,3,5-TIPBz.